University as a Global Brand: A Systematic Literature Review through the Brand Reputation Lens - Hasnizam Hasan (Semarak International Journal of Entrepreneurship, Economics, and Business Development, 2026)
Universities compete globally under intensifying pressure from massification, cross-border student mobility and ranking systems, yet existing brand theory only partially explains how institutional reputation is built and sustained. This paper reports a systematic literature review of 105 peer-reviewed studies published between 2000 and 2024, examining how four independent variables (artifacts, organisational values, organisational culture and customer experience) shape university brand reputation, with human capital as a moderating variable. Three structural patterns characterise the literature. Researchers rely predominantly on cross-sectional survey designs rather than tracking reputational shifts over time. Faculty and staff are consistently framed as vital institutional resources but rarely modelled as statistical moderators. Universities have adopted digital branding artifacts at scale without a theoretical framework to account for their reputational effects. Seven research gaps emerge from the synthesis: First, the absence of a validated multi-stakeholder brand reputation scale integrating all four independent variables. Second, the lack of longitudinal designs capable of tracing reputational trajectories across institutional life cycles and crisis events. Third, the untested moderating role of human capital between the four antecedents and brand reputation. Fourth, the scarcity of cross-cultural comparative studies, leaving Southeast Asian, African and Latin American contexts largely outside the theoretical conversation. Fifth, the absence of systematic theorisation linking digital artifacts to reputation outcomes. Sixth, the near-complete neglect of negative brand events (academic misconduct, rankings decline, leadership crises) and their reputational consequences. Finally, the unstudied relationship between staff diversity, as a dimension of human capital, and brand reputation. The first and third gaps carry the greatest theoretical weight. A conceptual framework integrating all six constructs is proposed to guide future empirical work.